A 2-year prospective densitometric study on the influence of Fok-I gene polymorphism in young patients with thalassaemia major. Issue 2 (February 2016) - Dimitriadou, M.; Christoforidis, A.; Fidani, L.; Economou, M.; Vlachaki, E.; Athanassiou-Metaxa, M.; Katzos, G.
Abstract Summary This study is to estimate the degree of genetic contribution of Fok-I gene polymorphism of Vitamin D receptor to bone mass in patients with thalassaemia. Results indicate a protective role of the f allele of the Fok-I gene polymorphism when found in homozygosity on bone mineral density of young thalassemic patients. Introduction The purpose of this study is to estimate prospectively the degree of genetic contribution of Fok-I gene polymorphism of vitamin D receptor (VDR) to the evolution of bone mass in patients with beta-thalassemia major (b-TH). Methods Sixty-four children and young adults (33 males and 31 females) with mean decimal age of 23.20 ± 5.41 (range 9.25–32.41 years) were recruited in this study. All patients were genotyping for Fok-I gene polymorphism and were assessed with dual energy X-ray absorptiometry (DXA) at baseline and 2 years after. Z-scores were calculated based on normal age and sex matched Caucasian population. Metabolites of vitamin D, intact PTH, total calcium, inorganic phosphorous, and alkaline phosphatase were measured at the serum pre-transfusion. Results A moderate proportion of patients had decreased DXA Z-scores (Z-score ≤−2) predominately in total hip (31 %) and secondary in lumbar spine (15.6 %). Patients being homozygous for the f allele had apparently higher BMD Z-scores compared with those carrying the F allele in homo- or heterozygosity, however, with a difference that did not reached significance. Interestingly enough, a significant deterioration in BMD Z-scores measured at femur (FF:P = 0.004 Ff:P < 0.001, ff:P = 0.024) and total hip (FF:P = 0.022, Ff:P = 0.005) was recorded for all type of genotypes, except for ff genotype and with regard to the total hip DXA values. An increased prevalence of serum 25(OH)D3 deficiency (59.4 %) and 25(OH)D3 borderline (12.5 %) was recorded. Conclusion Our study indicates a protective role of the f allele of the Fok-I gene polymorphism when found in homozygosity on bone mineral density of young patients with b-TM.